Strategic Analysis the Case of Mondelez International - Rihani, Michael (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Μηχανολόγων Μηχανικών, 2018)
Mondelēz International is one of the world's leading snack companies with an annual revenue of twenty-six billion dollars ($ 26B) approximately. It operates in more than 165 countries and leads in the categories of biscuits, chocolate, gum, candy and chocolate powder with products such as OREO, belVita, Cadbury, Milka and Trident. The aim of the following diploma thesis, which was elaborated within the framework of the Athens MBA graduate program, is multiple. Initially, it is important to analyze the company's creation through the mergers and acquisitions that have taken place, giving it the form it has today. The objective is to analyze and evaluate the existing strategy, taking into account both internal and external factors, so as to identify the competitive advantages of the company that have led to its success. Another objective is to analyze the category of chocolate in Europe and Greece by displaying statistical data while at the same time identifying elements and trends that serve to keep it at the top of the industry and continue its upward course. The final goal of this thesis is to draw conclusions and decompose individual elements that make Mondelēz a priority for consumer choices. More specifically, the first chapter of the work includes the creation of the company through the acquisition of Cadbury by Kraft and the presentation of the basic principles set by the new company, Mondelēz. In addition, the second chapter lists the mission, goals and vision for the company's future course and prosperity. Great emphasis is placed on the company's strategy to respond to changes in the market and consumer needs that vary according to country, age, season and more. A key example is the shift to safer, higher nutritional products and the emphasis on meeting conditions that are in line with the general environmental orientation. It also identifies the stakeholders who interact with the organization and rank in relation to their strength and influence. The SWOT analysis emphasizes the strengths of the company, its weaknesses, opportunities to exploit, and threats to be safeguarded. The context in which Mondelēz operates, which is influenced by political-economic changes, social factors, technological achievements, emerging environmental needs and changes in the legal order, seems to be of great importance. Work also includes the Porter analysis that explains the forces involved in the entry of new competitors, suppliers, buyers, substitute products as well as the competition of existing companies in the industry. In the third chapter we develop the competitive advantages of the company and focus on the company's development in relation to the competition in Europe in the chocolate category, which presents detailed statistics on market shares, financial data and a proposed development plan for the current year. Emphasis is placed on the structure of the market as we analyze the current state of chocolate in Europe and more specifically the five largest markets - Germany, England, France, Russia, Italy - accounting for 70% of the total European market. The fourth chapter deals with the situation in the Greek market and makes it clear which products thrive and produce more sales than the competitors. Distribution channels are mentioned from which the products are made accessible to the buying public as even how their placement on shelves and kiosks favors sales. The peculiarity of the Greek market is growing with regard to the seasonality of chocolate where there are fluctuations in sales depending on the season and the calendar holidays or the temperature that makes it less accessible in the summer months. In addition, there is a presentation of Mondelēz's products and other relevant competitive and a reference to the investment of each company in media advertisements.